Building a high resolution spectrometry system with lock-in detection technique - Nguyen, Binh The; Pham, Ben Van; Nguyen, Tuan Anh; Nguyen, Thanh Trong (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts